2007 ASME boiler & pressure vessel code : an international code. Section II, (American Society of Mechanical Engineers, 2008)
The international boiler and pressure vessel code establishes rules of safety governing the design, fabrication, and inspection of boilers and pressure vessels, the content is full-text searchable.